2020
DOI: 10.1038/s41467-020-17405-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale causal networks identify VGF as a key regulator of Alzheimer’s disease

Abstract: Though discovered over 100 years ago, the molecular foundation of sporadic Alzheimer's disease (AD) remains elusive. To better characterize the complex nature of AD, we constructed multiscale causal networks on a large human AD multi-omics dataset, integrating clinical features of AD, DNA variation, and gene-and protein-expression. These probabilistic causal models enabled detection, prioritization and replication of high-confidence master regulators of AD-associated networks, including the top predicted regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 91 publications
7
122
0
Order By: Relevance
“…Yet, a close correlation between NPTX2 and VGF was observed in cognitively healthy subjects, and this was maintained in both DLB and in AD, although somewhat weaker. Recently, VGF has been implicated as a master regulator of NPTX2 and BDNF [ 28 ], where BDNF itself also functions as regulator of both NPTX2 and VGF [ 18 , 26 ]. In this process, BDNF and VGF are seen as key regulators of neurogenesis, synaptic plasticity, and cognition [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, a close correlation between NPTX2 and VGF was observed in cognitively healthy subjects, and this was maintained in both DLB and in AD, although somewhat weaker. Recently, VGF has been implicated as a master regulator of NPTX2 and BDNF [ 28 ], where BDNF itself also functions as regulator of both NPTX2 and VGF [ 18 , 26 ]. In this process, BDNF and VGF are seen as key regulators of neurogenesis, synaptic plasticity, and cognition [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other candidate biomarker in the DLB proteomics study, VGF, is an interesting marker to compare to NPTX2, as its transcription is induced by neuronal growth factor (NGF) and BDNF [ 26 , 27 ]. This BDNF pathway is impacted in neurodegeneration, and VGF was implicated as a master regulator for NPTX2 [ 28 ]. VGF peptides are stored in dense core vesicles (DCVs), function as secretory peptide at synapses, and are important for a number of neuronal functions [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…K = 6 was used in this paper. This cutoff was chosen based on practical considerations (K will depend on the size and complexity of the network) and while we can use other cut-offs, K = 6 is commonly used in previous studies and is the default value suggested in the KDA software [ 9 , 26 , 83 , 84 ]. This K value is preferred because the key drivers within K steps can all be detected.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analysis, epidemiological studies, gene expression, and imaging in human patients demonstrate the contribution of glial cell dysfunction to neurodegeneration (Table S2). Genetic analysis using genome-wide associated studies identified a link between immune response and risk for AD [83]. Additionally, epidemiological studies linking the use of anti-inflammatory drugs with a decreased risk for dementia suggested that inflammation may be a contributing factor [84].…”
Section: Contribution Of Glial Cells To Human Neurodegenerative Diseasesmentioning
confidence: 99%